Transforming Whiteness: Exploring Transformation at Stellenbosch University - Verwoerd, Wian Brandt (Department of Political Studies, 2020)
As a historically Afrikaans university linked to the lingering legacies of Apartheid-era affiliation, Stellenbosch University (SU) faces harsh transformative realities. It has sought to tackle these realities through various policies and initiatives aimed at establishing (amongst others) diverse enrolment and racial inclusivity. Nevertheless, SU has consistently found itself embroiled in campus controversies over the past few years. More often than not, these controversies are ‘race’ related. As such, this thesis, by means of a theoretical case study, seeks to contextualise transformation at SU and questions its (in)efficacy thus far. The focus on transformation is divided into two levels: “institutional” and “relational”. The analysis of transformation in relation to these two levels is grounded in Critical Race Theory (CRT) and Critical Whiteness Studies (CWS), to try and illuminate novel areas of interest leading to nuanced, prospective, discussion. Using CRT, some of SU’s institutional attempts to transform are examined. A focus is placed on the Language Policy, given its central role in aiming to contribute to greater campus diversity. Amongst other findings, the lack of historical context contained within the various policy documents, in terms of highlighting Afrikaans’ stigmatic past, undermines the intent and efficacy of SU’s institutional transformation going forward. The Listen Live and Learn housing initiative is used as a starting point for a discussion on relational transformation. CWS is used as a lens to try and make sense of some of the individualised transformative shortcomings of the initiative. Whiteness, with a specific focus on Afrikaner whiteness, is established as a complex campus force that contains defensive elements in relation to transformation. These elements range from blatant resistance, to more latent elements such as fragility, guilt and shame. Often, these latent strategies come in discursive forms and are thus particularly unproductive in relation to transformation, as they serve to engender a lack of active and meaningful engagement. Nevertheless, elements of prospective transformative potential within whiteness are identified in relation to white fatigue. Finally, it is submitted that cautionary and effective engagement with whiteness offers a complimentary avenue on the road to achieving holistic transformation, in aiming to facilitate normative diversity on all fronts.